2018
DOI: 10.3345/kjp.2018.06765
|View full text |Cite
|
Sign up to set email alerts
|

The change of QRS duration after pulmonary valve replacement in patients with repaired tetralogy of Fallot and pulmonary regurgitation

Abstract: PurposeThis study aimed to analyze changes in QRS duration and cardiothoracic ratio (CTR) following pulmonary valve replacement (PVR) in patients with tetralogy of Fallot (TOF).MethodsChildren and adolescents who had previously undergone total repair for TOF (n=67; median age, 16 years) who required elective PVR for pulmonary regurgitation and/or right ventricular out tract obstruction were included in this study. The QRS duration and CTR were measured pre- and postoperatively and postoperative changes were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Apart from that, decreased QRS durations, or namely narrow QRS complexes, may be associated with aberrant conduction of supraventricular complexes. This is related to pneumonectomy [13][14][15]. Pmin indicates the minimum P wave duration.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, decreased QRS durations, or namely narrow QRS complexes, may be associated with aberrant conduction of supraventricular complexes. This is related to pneumonectomy [13][14][15]. Pmin indicates the minimum P wave duration.…”
Section: Discussionmentioning
confidence: 99%
“…QRS duration, mean pulmonary gradient, and the mean RV did not differ much between pre-and post-PVR procedures [17,[24][25][26]. Other studies have found that the QRS decreased significantly following PVR [8,14,27]. Aleligne et al observed that irrelevant of the type of procedure, there was a 6 ms decrease in the QRS duration in patients whose QRS was over 140 ms three years following surgery [27].…”
Section: Changes In Arrhythmias and Qrs Following Pulmonary Valve Rep...mentioning
confidence: 97%
“…The reasons for PVR following rTOF are severe PR and severe PR with pulmonary stenosis [ 8 ]. There are many indications for why surgery must occur, outlined in Table 1 .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation